Incidence of hyperkalemia RAASi and SGLT-2i treatment in individuals with diabetic kidney disease: a systematic review and network meta-analysis - Yahui Yuan; Yahui Yuan; Yahui Yuan; Chun Chen; Yuping Lin; Yehao Luo; Yehao Luo; Yehao Luo; Zhaojun Yang; Zhaojun Yang; Zhaojun Yang; Jingyi Guo; et al. (Frontiers in Pharmacology)
BackgroundThis study aims to evaluate the incidence of hyperkalemia and serum potassium levels associated with the use of sodium-glucose cotransporter-2 inhibitors (SGLT-2i), renin‐angiotensin‐aldosterone system inhibitors (RAASi) and concurrent use of these medications in individuals with diabetic kidney disease (DKD).MethodsA comprehensive systematic search was performed in EMBASE, the Cochrane Central Register of Controlled Trials (CENTRAL), Web of Science, Scopus, and PubMed database, covering studies up to March 2024. Relevant randomized controlled trials (RCT) included adults with DKD who were treated with SGLT-2i and RAASi or their combination, with a minimum follow-up duration of 12 weeks. The primary outcomes assessed were the incidence of hyperkalemia and serum potassium levels were the primary outcomes assessed. The surface under the cumulative ranking curves (SUCRA) was utilized for ranking purposes.ResultsThe study included 36 trials, encompassing 45,120 participants, comparing various interventions. SGLT-2i (SUCRA = 88.5%) was found to significantly reduce the risk of hyperkalemia. In contrast, the combination of ACEI/ARB + MRA (SUCRA = 5.7%) increased the risk of hyperkalemia. However, when SGLT-2i was added to the ACEI/ARB + MRA regimen, the incidence of hyperkalemia was found to decrease. Subgroup analyses on MRA showed that ACEI/ARB + spironolactone posed the highest risk of hyperkalemia. ACEI/ARB + SGLT-2i mitigated serum potassium level.ConclusionSGLT-2i was effective in reducing the incidence of hyperkalemia incidence, whereas a combination of ACEI/ARB and MRA might elevate the incidence of hyperkalemia in individuals with DKD.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/#recordDetails, identifier CRD42024552810.